2020
DOI: 10.7324/japs.2020.1010018
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and pharmacological properties of Curcuma aromatica Salisb (wild turmeric)

Abstract: Curcuma aromatica Salisb. (C. aromatica) is commonly known as wild turmeric. Curcuma aromatica is an essential herbal plant and it has been extensively used in traditional medicine for centuries. It has been used for the treatment of gastrointestinal ailments, arthritic pain, inflammatory conditions, wounds, skin infections, and insect bites. This article aims to review the phytochemical and pharmacological aspects of C. aromatica and to provide a guide and insight for further studies. Electronic repositories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…However, there are only a few works specifically dealing with the effect of Curcuma aromatica extracts. Analyses of the data showed that C. aromatica consists of various classes of compounds, including alkaloids, flavonoids, curcuminoids, tannins, and terpenoids, that formed the bases of its pharmacological activities [95]. Its content in curcuminoids (curcumin, bis-demethoxycurcumin and demethoxycurcumin) are lower than in C. longa [96], thus explaining a lower contribution from this phytochemical class when researching the bioactivities of this herbal medicine.…”
Section: Curcuma Aromaticamentioning
confidence: 99%
“…However, there are only a few works specifically dealing with the effect of Curcuma aromatica extracts. Analyses of the data showed that C. aromatica consists of various classes of compounds, including alkaloids, flavonoids, curcuminoids, tannins, and terpenoids, that formed the bases of its pharmacological activities [95]. Its content in curcuminoids (curcumin, bis-demethoxycurcumin and demethoxycurcumin) are lower than in C. longa [96], thus explaining a lower contribution from this phytochemical class when researching the bioactivities of this herbal medicine.…”
Section: Curcuma Aromaticamentioning
confidence: 99%
“…Turmeric ( Curcuma longa ) is rich in nutrients and contains carbohydrates, protein, vitamin C, polyphenols, beta-carotene, fatty acid volatile oils, and essential oils ( Patil et al, 2019 ; Umar et al, 2020 ). The bioactive substances in Curcuma longa are curcumin, tetrahydro curcuminoids, bisdemethoxycurcumin, and demethoxycurcumin ( Jyotirmayee and Mahalik, 2022 ).…”
Section: Background Informationmentioning
confidence: 99%
“…Curcuma aromatica Salisb., belonging to the genus Curcuma in the family Zingiberaceae, is distributed throughout the tropical and subtropical regions in the world and widely cultivated in Asian countries, especially in China, India, and Japan. [ 1 ] In Vietnam, this species, also known as “Nghệ trắng”, is popularly distributed in Quang Binh Province in the North and An Giang Province in the South. [ 2 ] Its rhizome is known as an aromatic medicinal herb.…”
Section: Introductionmentioning
confidence: 99%